My little pony : the movie [videorecording (DVD)] (Lions Gate Entertainment, 2018)
A dark force threatens Ponyville, and the Mane six embark on an unforgettable journey beyond Equestria where they meet new friends and exciting challenges on a quest to use the magic of friendship to save their home.